The Relationship Between Basic Locomotor Movement Ability and Learning Outcomes in Floor Gymnastics - Aceng Hilman; Toto Subroto; Marisa Novianti Fajrah Ilsya (Universitas Negeri Semarang, 2026)
Basic locomotor movement skills are part of fundamental movement skills (FMS), which develop in childhood and form an important foundation for mastering more complex specific motor skills. Basic movement skills that do not develop optimally will have a direct impact on children's ability to participate in more complex floor exercise activities. Therefore, in the context of physical education, especially floor gymnastics activities, the lack of readiness in basic locomotor skills has the potential to hinder the achievement of learning outcomes targeted by the curriculum. This study aims to determine the relationship between basic locomotor skills and learning outcomes in floor gymnastics activities. The method used in this study is a quantitative descriptive method with a correlational technique. The population in this study were students at Public Junior High School 40 Bandung, specifically those in grade VII, with a total of 290 students. The sample in this study used simple random sampling, with samples taken randomly by lottery, namely VII-A, which consisted of 32 students. The instrument used in this study to measure basic locomotor skills was the Test of Gross Motor Development (TGMD-2), while for learning outcomes in floor exercises, the researcher used assessments of knowledge, skills, and attitudes. The results of data analysis showed that the correlation coefficient of variable X with Y (rxy) was 0.603, which was categorized as having a strong correlation level, namely in the range of 0.60-0.799. This value also indicated a positive relationship between basic locomotor skills and learning outcomes in floor exercises.